Seepage Meters for Measuring Groundwater–Surface Water Exchange - Christopher J. Martinez (EDIS, 2010)
AE465, a 5-page illustrated fact sheet by Christopher J. Martinez, aids those who are engaged in surface water–groundwater exchange studies in cost-effective construction, installation, and use of seepage meters. Includes references. Published by the UF Department of Agricultural and Biological Engineering, July 2010.